EFEKTIVITAS PEMBELAJARAN LABORATORIUM BERBASIS PROYEK (PLBP) TERHADAP KREATIVITAS MAHASISWA - M. Zainudin (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
This apparent study is meant to prove the effectiveness of Project based laboratory Learning (PBLL) toward students’ creativity in Statistical Method I subject. The research’s populations are all second semester students from II-B and II-C. Data collection method used in this research are documentation and test. The research instruments are document and question test. The document in this research is used to determine the sample of the research through equilibrium analysis with the data collected from the students’ result of their study in the mathematics for School I for Junior and Senior High School. The test instrument is used to get the data related to students’ creativity. The result of this research shows that PBLL is more effective than direct learning to improve students’ creativity especially in the subject of Statistical method I.